Isoxazole derivatives as new nitric oxide elicitors in plants - Oancea, Anca; Georgescu, Emilian; Georgescu, Florentina; Nicolescu, Alina; Oprita, Elena Iulia; Tudora, Catalina; Vladulescu, Lucian; Vladulescu, Marius-Constantin; Oancea, Florin; Deleanu, Calin (Beilstein Journal of Organic Chemistry, 2017)
Several 3,5-disubstituted isoxazoles were obtained in good yields by regiospecific 1,3-dipolar cycloaddition reactions between aromatic nitrile oxides, generated in situ from the corresponding hydroxyimidoyl chlorides, with non-symmetrical activated alkynes in the presence of catalytic amounts of copper(I) iodide. Effects of 3,5-disubstituted isoxazoles on nitric oxide and reactive oxygen species generation in Arabidopsis tissues was studied using specific diaminofluoresceine dyes as fluorescence indicators.
Keywords: chemical elicitor; 1,3-dipolar cycloaddition; isoxazole; nitric oxide; nitrile oxide; reactive oxygen species